Sequences far downstream from the classical tRNA promoter elements bind RNA polymerase III transcription factors. - Young, L S (1991)
We have examined the interaction of transcription factors TFIIIC and TFIIID with a silkworm alanine tRNA gene. Previous functional analysis showed that the promoter for this gene is unusually large compared with the classical tRNA promoter elements (the A and B boxes) and includes sequences downstream from the transcription termination site. The goal of the experiments reported here was to determine which sequences within the full promoter make stable contacts with transcription factors. We show that when TFIIIC and TFIIID are combined, a complex is formed with the tRNA(Ala)C gene. Neither factor alone can form this complex. DNase I digestion of gene-factor complexes reveals that most of the tRNA(Ala)C promoter is in contact with factors. The protected region extends from -1 to at least +136 and includes both the A and B boxes and the previously identified downstream promoter sequences. Analysis of mutant promoters shows that sequence-specific contacts throughout the protected region are required for binding. The role of 3'-flanking sequences in transcription factor binding explains the contribution of these sequences to the tRNA(Ala)C promoter. We discuss the possibility that such sequences affect promoter strength in other tRNA genes.